Compression of Medical Images by Integer Wavelet Transform (International Journal of Engineering and Computer Science, 2016)
In today’s world of information exchange, Image compression has become an important process. It helps in effective utilization of high speed network resources. Medical image compression has an important role in medical field because they are used for future reference of patients. Medical data is compressed in such a way so that no medical information is lost. Medical imaging poses the great challenge of having compression algorithms that reduce the loss of fidelity as much as possible so as not to contribute to diagnostic errors and yet have high compression rates for reduced storage and transmission time. The medical image needs to undergo the process of compression before storing and transmitting it. Firstly, predictive encoding of the pixel values is done then it is transformed using wavelet transform after that obtained variables are encoded by an entropy encoder.